Parametrical experimental and numerical analysis on friction-induced vibrations by a simple frictional system. (August 2017) - Di Bartolomeo, M.; Lacerra, G.; Baillet, L.; Chatelet, E.; Massi, F.
Abstract: This paper presents an experimental and numerical analysis on friction-induced vibrations arising from the frictional contact between two bodies in relative motion. The sliding contact has been reproduced within a mechanical system characterized by a simple dynamics, in order to better distinguish between the dynamic response of the system and the broadband excitation coming from the contact. The effects of some parameters, mainly relative velocity, roughness and normal load, on the magnitude and frequency content of the induced vibrations are investigated, also by comparing results from experimental measurements and simulations. A distinction between weak and strong coupling is recovered by the experimental results. Finally, accounting for the contribution of the roughness to the contact-induced vibrations, a conceptually innovative method to implement the effect of the roughness in the numerical simulation is proposed. Highlights: An experimental and numerical analysis on Friction Induced Vibrations is proposed. The effect of different boundary conditions has been investigated. A distinction between weak and strong coupling is recovered. A new method to implement the roughness in the numerical simulation is addressed.